2015
DOI: 10.1109/tps.2015.2422779
|View full text |Cite
|
Sign up to set email alerts
|

The Configuration Effects of Electrode on the Performance of Dielectric Barrier Discharge Reactor for NO<sub><italic>x</italic></sub> Removal

Abstract: In this paper, a dielectric barrier discharge cylindrical reactor has been analyzed in order to increase the efficiency of nitrogen oxide (NO x ) removal from the simulated gas under the room temperature. The effects of electrode shape as well as electrode diameter and electrode length are investigated in the nonthermal plasma reactor. Two different electrode configurations (rod and screw thread electrodes) are examined. The experimental result shows that for the rod electrode, NO x removal efficiency is enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…1-a and 1-b, respectively. The setup consists of the DBD reactor, high voltage pulse power generator, gas feeding system and the measurement system [25]. The plasma reactor used in the present study is a DBD reactor, which is shown in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1-a and 1-b, respectively. The setup consists of the DBD reactor, high voltage pulse power generator, gas feeding system and the measurement system [25]. The plasma reactor used in the present study is a DBD reactor, which is shown in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
“…The other gas components of NOx cylinder are N2, H2O, N2O, and CO2. The amount of each gas contained in the NOx cylinder can be found in [25]. The gas system was sealed precisely in order to prevent any gas leakage from the joints and tubes [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport equation of electron and electron energy in the fluid model is obtained from a two-order approximate solution of the Boltzmann Equation [17], as shown in Equations (1) and (2):…”
Section: Governing Equationsmentioning
confidence: 99%
“…The electron energy usually comes from the acceleration of electrons by an external electric field. Recent studies have shown that NTP has good performance for the removal of gaseous pollutants such as NO and SO 2 [1][2][3], and industrial demonstration applications have been carried out because of its compact structure and high energy-efficiency [4,5]. Gas discharge at atmospheric pressure is the most common form of NTP used for flue gas treatment, such as corona discharge, dielectric barrier discharge, and so on [6,7].…”
Section: Introductionmentioning
confidence: 99%